Evaluation of Growth, Yield and Quality of Turmeric Genotypes (Curcuma longa L.) - Sagor, Md. Shaheeduzzaman; Hossain, Md. Mokter; Haque, Tamanna (Journal of Tropical Crop Science, 2021)
This study was conducted to examine growth, yield and quality performances of five turmeric genotypes. The experiment was laid out in randomized complete block design with three replications. Results showed that different genotypes significantly influenced on plant growth, yield and quality of turmeric. The highest germination (97 %), number of leaves (8.16), plant height (69.51 cm), weight of rhizome (47.06 g/plant) and yield (6.01 t/ha) was found from “Sinduri Holud” (BARI Holud-2). But this genotype scored the lowest percentage in curcumin (0.30 %) and low dry matter (22.54 %). While local genotype (“Mota Holud”) performed the lowest germination (87.57 %) and minimum plant height (53.52 cm), leaf area (127.42 cm2), number of fingers per rhizome (3.73), weight of rhizome (34.16 g/plant) and yield (4.78 t/ha). But this genotype contained the highest curcumin (2.10 %), and “Mala Holud” attained maximum dry matter (25.20%). Based on flesh color, dry matter and curcumin contents local turmeric genotypes performed superior than that of the check varieties. From the findings of this investigation, it can be concluded that local genotypes can be used in breeding program for development of high quality turmeric in Bangladesh.